Capital social e desenvolvimento sustentável: uma análise da implementação da Agenda 2030 na Unioeste - Christ, Gabriela Daiana (2022)
The 2030 Agenda for sustainable development (also known as the Sustainable Development Goals – SDGs) draws attention to learning opportunities throughout its implementation process. The 2030 Agenda – proposed by the United Nations in 2015 – suggests that everyone (government, civil society, etc.) should act towards a more sustainable world. In this scenario, Higher Education Institutions (HEIs) are inserted, the way HEIs are dealing with this is an open question. Thus, the objective of this research was to analyze the implementation of the Sustainable Development Goals at the Western Paraná State University (Unioeste) under the influence of social capital. To meet the objective of this case study with a qualitative approach, semi-structured interviews were used as a data collection technique with fourteen managers who are in a leadership role at Unioeste. Data analysis was done through content analysis and supported using Altas.ti software. The results showed that Unioeste has the necessary social capital, but not enough for the implementation of the SDGs at the University. That is, although, in a reactive way, Unioeste contributes to the implementation of the SDGs in the institution, which in turn reverberates in the spaces it occupies. Putting social capital at the center of this revision is one way (not the only one) forward. This research theoretically contributed to a better understanding of the implementation of the SDGs in universities, strengthening research on the subject that is considered multidisciplinary. In practice, this study has a managerial contribution as it can support decision-making regarding sustainability management at the University and could help to raise awareness of issues on the institution's agenda, that is, the first step towards action (understanding), facing the challenges that sustainability proposes. It is concluded that the studies are not exhausted since there is still a need to expand research on the subject in higher education institutions.